1981
DOI: 10.1136/jcp.34.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Combination of minocycline and rifampicin against methicillin- and gentamicin-resistantStaphylococcus aureus

Abstract: Methicillin- and gentamicin-resistantStaphylococcus aureusmay remain sensitive to minocycline and to rifampicin. A study of growth curves has shown that at inhibitory concentrations (0·4 μg/ml), minocycline prevents the development of mutants resistant to rifampicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Unlike heavily contaminated areas such as the gastrointestinal tract, catheters are rarely heavily colonized or exposed to highgrade bacteremia (27). In vitro (24,30) and in vivo (3,5) studies have demonstrated that minocycline protects against the emergence of staphylococcal strains that are resistant to rifampin. In addition, neither rifampin nor minocycline was found to be associated with cross-resistance to other betalactam or glycopeptide antibiotics (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike heavily contaminated areas such as the gastrointestinal tract, catheters are rarely heavily colonized or exposed to highgrade bacteremia (27). In vitro (24,30) and in vivo (3,5) studies have demonstrated that minocycline protects against the emergence of staphylococcal strains that are resistant to rifampin. In addition, neither rifampin nor minocycline was found to be associated with cross-resistance to other betalactam or glycopeptide antibiotics (7).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the combination of minocycline and rifampin has occasionally been shown to be synergistic (24,30) but never antagonistic. In a recent susceptibility study of 197 methicillin-resistant and methicillin-susceptible S. epidermidis and S. aureus bacteremic isolates from the M. D. Anderson Cancer Center, the MICs of minocycline, rifampin, and ciprofloxacin at which 90% of strains are inhibited were 1.0, 0.5, and 32.0 g/ml, respectively (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, literature is having quite a number of reports reporting primary MRSA resistance to rifampin as well as following combination therapy (Yourassowksy et al 1981, Gottlieb et al 1998, Aucken et al 2002, Norazah et al 2002, Srinivasan et al 2006. A study has shown emergence of rifampin resistance to MRSA in tuberculosis wards.…”
Section: Peter F M Choongmentioning
confidence: 99%
“…Although it has been shown that these resistant strains exhibit poor carrier colonizing potential (21,22), only a small number of colonized personnel are necessary to perpetuate an outbteak (17,19). Reporting on a large outbreak of multiply antibiotic-resistant S. aureus, Locksley et al (19) have found that the outbreak was controlled only (2,18,20,25,39). For this reason, in addition to the potential renal and hepatotoxic problems associated with use of rifampin, it is generally recommended that it be used to eradicate colonization only in high-risk situations, and then only in combination with an additional antistaphylococcal antibiotic (19,20,39).…”
Section: Discussionmentioning
confidence: 99%
“…Reporting on a large outbreak of multiply antibiotic-resistant S. aureus, Locksley et al (19) have found that the outbreak was controlled only (2,18,20,25,39). For this reason, in addition to the potential renal and hepatotoxic problems associated with use of rifampin, it is generally recommended that it be used to eradicate colonization only in high-risk situations, and then only in combination with an additional antistaphylococcal antibiotic (19,20,39). Rifampin in combination with trimethoprim-sulfamethoxazole has been used successfully to eradicate the carrier state in patients colonized at both nasal and extranasal sites (31).…”
Section: Discussionmentioning
confidence: 99%